A practical guide to groundwater and solute transport modeling - Spitz, Karlheinz 1955- (John Wiley & Sons, 1996)
Focusing on modeling applications, this outstanding reference provides a step-by-step, non-mathematical approach to constructing and using realistic workable groundwater models on a daily basis. Extensive detailed drawings, case studies, practical examples, and sample models illustrate important concepts. Includes data on hydrogeologic features and pollutants plus a glossary of terms.